2001
DOI: 10.1046/j.1365-2141.2001.02963.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a role for a non‐matrix‐type metalloproteinase activity in the shedding of syndecan‐1 from human myeloma cells

Abstract: Summary. Syndecan-1 is a cell surface proteoglycan that is expressed on human myeloma cells and is thought to act as a co-receptor for certain extracellular matrix proteins and growth factors. The ectodomain of syndecan-1 is thought to be shed from the surface of myeloma cells, although the exact mechanism of release remains unclear. In this study, we used a panel of inhibitors to identify the class of proteinase responsible for shedding the soluble syndecan-1 ectodomain from human myeloma cells. Using enzymel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…In particular, ERK1/2 and PKC signaling have been shown to be required for RANTES-induced shedding of syndecan-1 and syndecan-4 in HeLa cells (5) and for EGF-and thrombin receptor-induced shedding in mouse epithelial cells (8). Most other reports on the mechanism of syndecan shedding have focused on the involvement of intracellular protein tyrosine kinase (29) and matrix metalloproteinase (MMP) (1,11,21) activity in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ERK1/2 and PKC signaling have been shown to be required for RANTES-induced shedding of syndecan-1 and syndecan-4 in HeLa cells (5) and for EGF-and thrombin receptor-induced shedding in mouse epithelial cells (8). Most other reports on the mechanism of syndecan shedding have focused on the involvement of intracellular protein tyrosine kinase (29) and matrix metalloproteinase (MMP) (1,11,21) activity in this process.…”
Section: Discussionmentioning
confidence: 99%
“…20 Others have demonstrated that syndecan-1-transfected ARH-77 B-lymphoid cells are less invasive than the wild-type cells, which have no endogenous syndecan-1. 33 Syndecan-1 is also constitutively shed from the cell surface, 34,35 and ARH-77 cells engineered to produce a soluble form of this transmembrane heparan sulfate proteoglycan are hyperinvasive. 36 The proliferation of the 5T2MM cells increased during the disease progression, parallel with their differentiation into CD45 Ϫ cells.…”
Section: Discussionmentioning
confidence: 99%
“…5 Total PKC activity has been reported to be elevated in carcinomas of breast 6 and lung. 7 In MM, PKC has been implicated in the shedding of CD138 8 and the IL-6 receptor, 9 both of which are thought to play important roles in tumor progression. Eleven isoforms of PKC have been identified, and these have been separated into 3 subgroups: (1) the conventional calcium-dependent and DAG (diacylglycerol)-dependent PKCs (cPKCs: ␣, ␤ I , ␤ II , ␥), (2) the nonconventional calcium-independent but DAG-dependent PKCs (nPKCs: ␦, ε, , , ), and (3) the atypical calcium-independent and DAGunresponsive PKCs (aPKCs: , ).…”
Section: Introductionmentioning
confidence: 99%